Pengaruh Pendidikan, Pelatihan, dan Pengalaman Terhadap Skeptisisme Profesional Auditor Pada KAP di Kota Batam - Kezia Violin; Poniman Poniman (Komunitas Dosen Indonesia, 2024)
Maintaining an inquisitive mindset while presenting audit data critically is an approach that displays professional skepticism. To approve or reject findings by offering corrective measures, the auditor must first gather information about the activities of the audited organization, compare it with predetermined criteria, and then draw conclusions. An auditor has an obligation to uphold his profession by doing what is asked of him. In addition to stating consideration for the reliability of financial statements, it is their professional duty to adhere to the. The public and consumers alike will evaluate certified financial reports, so it is important to approach such reports with a healthy level of skepticism. The main objective of this research is to determine whether the professional skepticism of auditors at KAP in Batam City varies according to level of education, training and work experience. Saturated sampling was used to determine the sample size of 45 respondents for this quantitative research procedure. Using SPSS 26 software, this reconnaissance yielded considerable results. Education has a significant positive effect because the T test value of 0.031 is less than 0.05. Since the calculated T value of 0.000 is lower than 0.05, this indicates that training has a statistically significant positive impact. The stay experience is positive with a T test score of 0.000, lower than the significance level of 0.05. With an F significance level of 0.00 which is less than 0.05, the F test shows that the auditor's education, training and experience influence their professional skepticism. Therefore, auditors' professional skepticism is significantly influenced by their education, training, and experience. The elements influencing auditors' professional skepticism may be better understood with these data.